The Future of Double Consciousness: Epistemic Virtue, Identity, and Structural Anti-Blackness - Emmalon Davis; Orlando Hawkins (Ergo, An Open Access Journal of Philosophy)
This paper considers two conceptual expansions of Du Boisian double consciousness—white double consciousness (Alcoff 2015) and kaleidoscopic consciousness (Medina 2013)—both of which aim to articulate the moral-epistemic potential of cultivating double consciousness from racially dominant or other socially privileged positions. We analyze these concepts and challenge them on the grounds that they lack continuity with their Du Boisian predecessor and face problems of practical feasibility. As we show, these expansions obscure structural barriers that make white double consciousness and kaleidoscopic consciousness unlikely antidotes to the kind of racial domination that double consciousness was introduced to illuminate. We conclude that while more intersectional and pluralistic accounts of double consciousness may be desirable, the project of expansion has moral limits. Identifying these limitations, we outline ways in which double consciousness—as a tool for conceptualizing the genealogy of structural anti-Blackness—remains valuable in the absence of ever-expanding revision.